Evaluation of Madrasah Based Management Programs in Private Aliyah Madrasah in Central Lombok Regency - Suhardi, Muhamad; Mulyadi, Didi; Huda, Syafaat Ariful; Nazopah, Nada (Jurnal Kependidikan : Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran, dan Pembelajaran, 2020)
The objectives of this research are to understand, explain and improve Madrasah based Management Program (Islamic Concept). The research used qualitative approach which used evaluation model of CIPP (Context, Input, Process and Outcome). It was conducted at Islamic High School Jonggat sub-district. Instruments used were observation and deep interview technique. The results were that some weaknesses of programs in the effort of increasing teacher’s human resources that were not mastering learning model media (coul not operate the laptop and in focus), increasing the facilities need and low cost. Recommendations; it is suggested to those who are in the stakeholders to pay attention to this issue. So, the implementation of the program could be done successfully later.